THE INFLUENCE OF USING THE LESSON METHOD ON STUDENTS IN INCREASING THE LEARNING OF MORAL THEOLOGY IN THE PANDEMIC TIME OF COVID-19 - Sitti Aisyah Abbas; Akramun Nisa; Suparman Mannuhung; Indah Indah (Universitas Andi Djemma, 2023)
This research deals with the application of the Lecture Method to learning the Moral theology. The purpose of this research is to know the influence of the lecture method in improving the lessons of the Moral theology for students. To answer these problems the author uses a type of quantitative descriptive research, to obtain data sources there are two data sources, namely primary data and secondary data. The technique used in data collection is in the form of a questionnaire. The population used in this study were 338 respondents, while the sample was 30 respondents. The technique of determining the sample, namely by random sampling. As for the process of data analysis,According to the results of the study, it was found that the frequency of the x variable obtained the percentage of respondents as much as 8.81 percent for the lecture method, while the results of calculating the data frequency for variable Y obtained the percentage of respondents as much as 91.21 percent. this means that the hypothesis rejects Ho and accepts Ha, that is, there is the influence of the lecture method in understanding the lessons of moral ethics. The lecture method has a significant influence on learning the moral creed. Therefore it can be concluded that the lecture method is very influential on students in learning the Moral theology.